NSUN6 expression correlates with prognosis and immune infiltration in human cancers based on pan-cancer analysis - Jie Gao; Yao Xu; Chan Tian; Qiuhong Zhang; Ming Zhang; Hu Shan; Jie Shi; Zongjuan Ming; Shuanying Yang; Xia Yang (Scientific Reports)
Abstract Background NSUN6 is a regulator of tRNA methylation that partially exists in the Golgi and centrosomes. It catalyzes the methylation of tRNACys and tRNAThr at the C72 site, which affects tRNA generation. However, its expression, prognosis, and immune invasion in pan-cancer have not been studied. This extensive research tapped into the TCGA database, gathering 33 carefully paired sets of cancer and nearby normal tissues, covering a broad spectrum of 33 different cancer types. Moreover, this study explored how NSUN6 expression relates to the presence of immune and stromal cells in the tumor’s intricate immune environment. To further understand NSUN6’s role, a detailed Gene Set Enrichment Analysis (GSEA) was conducted, revealing its enrichment patterns in various carcinoma subtypes and hinting at its involvement in tumor growth. Analysis of NSUN6 expression patterns revealed a significant increase in eight cancer types, including lung adenocarcinoma and pancreatic cancer (P < 0.001). Additionally, a reduction was observed in six cancer types, such as cholangiocarcinoma and thyroid cancer (P < 0.001). Survival analysis indicated that individuals with lung adenocarcinoma, pancreatic cancer, and other cancers expressing high levels of NSUN6 had improved prognosis. The association between NSUN6 expression and patient outcomes was evident, including overall survival, disease-specific survival, disease-free interval, and progression-free interval. Furthermore, individuals with high levels of NSUN6 expression showed significantly longer survival times than those with low levels (P < 0.05). The involvement of NSUN6 in immune infiltration was evident, GSEA showed a significant correlation between NSUN6 expression and the five most significant enrichment pathways in different tumors. The NSUN6 gene functions as an initial indicator for diagnosis in renal clear cell carcinoma, pancreatic cancer, lung adenocarcinoma, and low-grade brain glioma. There is an association between its elevated expression and the predictive outcome, as well as the immune system’s infiltration, in 33 varieties of cancer. This study is limited by its reliance on in silico analyses without experimental validation. Additionally, the use of publicly available datasets may introduce variability due to differences in data sources and platforms.